STRATEGI PENDIDIKAN KARAKTER MELALUI MIND MAPPING BERBASIS MINDJET MIND MANAGER UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA PADA KONSEP DASAR MANAJEMEN PERKANTORAN - Oktarina, Nina; Kuswantoro, Agung (Universitas Negeri Semarang, 2013)
The purposed of this research are: 1) how the implementation of the strategy of character education through learning-based mind mapping with Mindjet Mind Manager, 2) the extent of implementation of the strategy of character education through learning-based mind mapping with Mindjet mind manager in improving students’ understanding of the concept of office management, 3)What values are embedded in the learning based mind mapping with mindjet mind manager. This research is classroom action research. The results showed that: 1) Implementation of character education through learning-based mind mapping with Mindjet mind manager implemented with methods of theory and practice in the learning process, so that students in a creative character, respect other people’s work, honest, confident and brave their ideas and ideas can be formed, 2) learning-based mind mapping with Mindjet mind manager is highly effective in improving students’ understanding of the basic concepts of management offices. It also increases the activity and attention of students during the learning process and the learning ability of lecturer in management,3)character values that are embedded in the learning process is self-reliance, hard work, creativity, honesty, respect other people’s work, critical. Advice related to the results of this study are: 1) At the time of implementing the learning-based mind mapping with Mindjet mind manager should facilities and infrastructure such as the Internet must be available and connected to the well, 2) For optimum learning more, at the beginning of the lecture lecturer should provide examples of using the program prior to the student with coherent phase.